Considering the Role of Extracellular Matrix Molecules, in Particular Reelin, in Granule Cell Dispersion Related to Temporal Lobe Epilepsy - Leifeld, Jennifer; Förster, Eckart; Reiss, Gebhard; Hamad, Mohammad I. K. (Frontiers in Cell and Developmental Biology, 2022)
The extracellular matrix (ECM) of the nervous system can be considered as a dynamically adaptable compartment between neuronal cells, in particular neurons and glial cells that participates in physiological functions of the nervous system. It is mainly composed of carbohydrates and proteins that are secreted by the different kinds of cell types found in the nervous system, in particular neurons and glial cells, but also other cell types, such as pericytes of capillaries, ependymocytes and meningeal cells. ECM molecules participate in developmental processes, synaptic plasticity, neurodegeneration and regenerative processes. As an example, the ECM of the hippocampal formation is involved in degenerative and adaptive processes related to epilepsy. The role of various components of the ECM has been explored extensively. In particular, the ECM protein reelin, well known for orchestrating the formation of neuronal layer formation in the cerebral cortex, is also considered as a player involved in the occurrence of postnatal granule cell dispersion (GCD), a morphologically peculiar feature frequently observed in hippocampal tissue from epileptic patients. Possible causes and consequences of GCD have been studied in various in vivo and in vitro models. The present review discusses different interpretations of GCD and different views on the role of ECM protein reelin in the formation of this morphological peculiarity.